Comparison Of Acetic Acid With As Formiic Acid Latex Pump Material - Rudi Munzirwan (Universitas Negeri Medan, 2021)
Research on the comparison of acetic acid and formic acid as a latex coagulant has been carried out. To the latex coconut shell charcoal (particle size 80 mesh) was added to the weight of 42 grams then the latex was coagulated with acetic acid and formic acid with a pH of 4.7. As a research, the quality of rubber was carried out by measuring the initial plasticity, plasticity retention index and viscosity of rubber mooney. Finally, latex coagulated with acetic acid produced a better rubber than latex coagulated with formic aci).